The Relationship Between Knowledge Sharing and Organizational Prosperity: Analytical: Research in The State Company for Electrical and ElectronicIndustries (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of the research is to investigate the correlation and influencebetween knowledge sharing and organizational prosperity in the General Company for Electricaland Electronic Industries, and to identify the nature and pattern of thinking prevailing atthe different levels in the concerned company, and the extent of its members’ participation witheach other ,consolidating the culture of knowledge sharing and directing it towards achievingorganizational prosperity.The data was collected from)166(respondents represented by apurposive sample of senior and middle management, and for data analysis, statistical programswere added .SPSS, AMOS )by adopting appropriate statistical methods .The results showed thevalidity of correlation and influence relationships at the level of the main variables and subdimensions,which indicates the essential role of knowledge sharing toachieve organizational prosperity in the company